Atypical presentations of UTUC: a case report of three patients - Guo, Linfa; Bai, Xiaojie; Tuoheti, Kuerban; Wang, Xiaolong; Liu, Tongzu (Frontiers in Oncology, 2024)
Upper tract urothelial carcinoma (UTUC) is a rare clinical condition primarily characterized by symptoms such as gross or microscopic hematuria, flank pain, and renal colic. Although computed tomography urography (CTU) is currently the most accurate imaging modality for diagnosis, atypical presentations and physical examination findings can sometimes obscure lesions, posing diagnostic challenges.In this report, three patients exhibited atypical symptoms, sharing a common complaint of flank pain.Notably, the first patient, who had recently undergone laparoscopic right duplex nephrectomy, presented with microscopic hematuria, whereas the other two did not show any gross or microscopic hematuria. Computed tomography urography revealed hydronephrosis and infection without significant renal pelvic space-occupying lesions, with persistently elevated white blood cell (WBC) counts, but no fever. These atypical clinical presentations confounded clinicians, delaying the diagnosis of upper tract urothelial carcinoma until postoperative pathological examination for the first two patients and resulting in advanced-stage diagnosis for the third patient. Postoperative pathology confirmed high-grade invasive upper tract urothelial carcinoma in all three patients.Upper tract urothelial carcinoma can manifest atypically without hematuria and may be challenging to visualize on computed tomography urography, potentially leading to misdiagnosis. Therefore, clinicians should maintain a high level of suspicion for malignant tumors when patients exhibit hydronephrosis, infection on imaging, and persistently elevated white blood cell counts without fever, even in the absence of typical signs of upper urothelial carcinoma on computed tomography urography.